Transportation Affected on Binjai City Development - Siregar, Achmad Haryansyah; Badaruddin, Badaruddin; Tarmizi, Tarmizi; Purwoko, Agus (International Conference on Sciences Development and Technology, 2021)
This research is a questionnaire survey research. This research was conducted with the aim of knowing the effect of transportation on regional development in Binjai City. The population in this study are transportation stakeholders in Binjai City. The number of samples in this study was determined using the Monte Carlo sample method with a sample size of 100 respondents. The data in this study were analyzed using descriptive statistical analysis and simple linear regression analysis. The hypothesis was tested using the t test. Based on the results of the analysis conducted, it is revealed that empirically transportation has a significant positive effect on regional development in Binjai City. By improving good transportation, regional development will also be better.